1992
DOI: 10.1111/j.1432-1033.1992.tb16887.x
|View full text |Cite
|
Sign up to set email alerts
|

Swainsonine is a useful tool to monitor the intracellular traffic of N‐linked glycoproteins as a function of the state of enterocytic differentiation of HT‐29 cells

Abstract: After treatment with swainsonine, an inhbitor of both lysosomal a-mannosidase and Golgi a-mannosidase-I1 activities, analysis of [3H]mannose-labeled glycans showed that HT-29 cells, derived from a human colonic adenocarcinoma, displayed distinct patterns of N-glycan expression, depending upon their state of enterocytic differentiation. In differentiated HT-29 cells hybrid-type chains were detected, whereas undifferentiated HT-29 cells accumulated high-mannose-type oligosaccharide, despite our demonstration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…Loss of activation of ERK1/2 is an important event during the differentiation process of HT-29 cells in goblet cells and enterocytes. This downregulation of ERK1/2 is in agreement with the previously reported decrease in macroautophagy during the differentiation process of HT-29 cells (49). In addition, blockade of the ERK1/2 pathway suppresses the growth of colon tumors and the invasiveness of HT-29 cells (54).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Loss of activation of ERK1/2 is an important event during the differentiation process of HT-29 cells in goblet cells and enterocytes. This downregulation of ERK1/2 is in agreement with the previously reported decrease in macroautophagy during the differentiation process of HT-29 cells (49). In addition, blockade of the ERK1/2 pathway suppresses the growth of colon tumors and the invasiveness of HT-29 cells (54).…”
Section: Discussionsupporting
confidence: 92%
“…Amino acid-dependent inactivation of PP2A would suppress macroautophagy by down-regulating ERK1/2 signaling and by up-regulating mTOR/p70 S6 kinase signaling. This hypothesis is in line with the inhibitory effect of okadaic acid on the macroautophagic pathway in liver cells (48) as well as in human intestinal cell lines (49). However, inhibition of other PP2A-dependent events such as the control of the intermediate filament network cannot be excluded in the inhibition of the formation of autophagic vacuoles as suggested in liver cells (50,51).…”
Section: Discussionsupporting
confidence: 61%
“…14 C]valine-labeled cells (40,46). Autophagic protein degradation could be inhibited to uninduced levels by the addition of either wortmannin or leupeptin to the EBSS starvation medium, while, in contrast, the proteasomal inhibitor lactacystin did not show any inhibition (data not shown).…”
Section: Screen Of Human Kinome For Autophagy Modulators-tomentioning
confidence: 88%
“…20 and references therein for a recent discussion), these vacuoles acquire lysosomal enzymes by either direct fusion with lysosomes (21)(22)(23) or late endosomes/prelysosomes (24). We have previously shown that the impairment of N-linked glycoprotein processing (25)(26)(27) in undifferentiated HT-29 cells is the consequence of a constitutive autophagic pathway (28). Recently, we have shown that autophagic sequestration is controlled by a G i3 protein in this cell line (29).…”
mentioning
confidence: 99%